Stability-Indicating RP-HPLC Method for Simultaneous Quantification of Ombitasvir, Paritaprevir and Ritonavir in Tablet Dosage Form - Kuna, Mangamma; Dannana, Gowri Sankar (Asian Journal of Chemistry, 2018)
A new stability indicating RP-HPLC method has been developed for simultaneous estimation of ombitasvir, paritaprevir and ritonavir in bulk and tablet dosage form. The method involves separation and analysis of the selected drugs on Inertsil ODS C18 (4.6 mm × 250 mm, 5 μm). The optimized mobile phase consists of orthophosphoric acid (40 %): acetonitrile (60 %) with a flow rate of 1 mL/min and detection at 252 nm. Retention time was 2.056 min for ombitasvir, 2.821 min for paritaprevir and 4.853 min for ritonavir. The developed method was validated as per the ICH guidelines. Linearity was observed in the range of 6.25-31.25 μg/mL for ombitasvir, 37.5-187.5 μg/mL for paritaprevir and 25-125 μg/mL for ritonavir with good correlation coefficient value (> 0.9990). The percentage recoveries of ombitasvir, paritaprevir and ritonavir were in the range of 99.98-100.69 %, 99.16-100.75 % and 99.82-100.08 %, respectively. The percentage relative standard deviation was < 2 %. The method had the ability to quantify the drugs simultaneously from tablets dosage forms with no interference from the tablets excipients. Ombitasvir, paritaprevir and ritonavir were also subjected to acid, base, oxidation and thermal degradation studies. The proposed method effectively analyzed the studied drugs in the presence of their degradation products.